Supragastric belch may be related to globus symptom – a prospective clinical study. Issue 5 (6th January 2016) - Nevalainen, P.; Walamies, M.; Kruuna, O.; Arkkila, P.; Aaltonen, L.‐M.
Abstract: Background: The etiology of globus is poorly understood. It is controversial, whether gastroesophageal reflux disease (GERD) has a role in globus. To investigate the possible esophageal background of this symptom, we performed transnasal esophagoscopy (TNE), high‐resolution manometry (HRM), and 24‐h multichannel intraluminal impedance (MII) and pH monitoring on globus patients. Methods: Thirty consecutive patients were referred to Helsinki University Hospital, Department of Otorhinolaryngology – Head and Neck Surgery for treatment of globus; 24 consecutive patients with difficult reflux symptoms from the Department of Surgery served as controls. We compared the results of the patient groups in endoscopies, HRM, and 24‐h MII‐pH monitoring. Key Results: In MII monitoring, globus patients had supragastric belch (6/20, 30% vs 1/24, 4%; p = 0.038) more often than controls. Total reflux time was higher in controls ( p = 0.004), and they had more acid reflux events ( p = 0.002) in MII, but between groups, the number of non‐acid reflux events was similar. In pH monitoring, DeMeester score and total pH <4 time were higher in controls ( P < 0.001). In HRM, the upper esophageal sphincter (UES) mean basal and residual pressures did not differ. Conclusions & Inferences: Supragastric belch was more common in globus patients, suggesting the possible role of this condition in globus sensation. However, globus patients in this series had no acid or non‐acid GERD or elevated UES pressure. Abstract : The aim was to investigate the possible esophageal background of globus symptoms, patients with reflux symptoms served as controls. In this study, globus patients without reflux symptoms did not have acid or non‐acid GERD in 24‐h MII‐pH monitoring. However, globus patients had supragastric belch more often than patients with reflux symptoms.